Rapid and Quantitative Assessment of Redox Conduction Across Electroactive Biofilms by using Double Potential Step Chronoamperometry. Issue 5 (27th February 2017) - Zhang, Xu; Philips, Jo; Roume, Hugo; Guo, Kun; Rabaey, Korneel; Prévoteau, Antonin
Abstract: The mechanism of electron transport across electroactive biofilms (EABs) is of high interest and still a matter of debate. Quantitative assessments of their redox conduction take considerable time and require non‐turnover conditions (absence of substrate), which can be detrimental to EABs. Here, we measure the charge‐transport parameters of Geobacter spp. dominated EABs with double potential step chronoamperometry (DPSC) with Cottrell analysis. The DPSC measurement is simpler and much faster than usual techniques and allows the determination of the charge‐transport parameters even under turnover conditions. The electrochemical responses were well‐described by a model of redox conduction driven only by electron diffusion within the EAB. The apparent diffusion coefficient for the electron ( D app ) was measured as approximately 3.2×10 −7  cm 2  s −1, a value similar to those recorded for pure Geobacter sulfurreducens EABs, or for some redox polymers with comparable redox center concentrations. This method will be valuable for assessing the impact of EAB characteristics and environmental factors on the charge‐transport ability of the biofilm, and for determining the rate‐limiting step(s) for current production. Abstract : Who's in charge? Double potential step chronoamperometry follows the Cottrell equation and provides charge‐transport parameters in electroactive biofilms dominated by Geobacter spp., as predicted by the model of redox conduction. The method is much faster and simpler than previous techniques and can even be performed in presence of substrate (turnover condition).